Scale of emotional development—Short. (December 2016) - Sappok, Tanja; Barrett, Brian Fergus; Vandevelde, Stijn; Heinrich, Manuel; Poppe, Leen; Sterkenburg, Paula; Vonk, Jolanda; Kolb, Juergen; Claes, Claudia; Bergmann, Thomas; Došen, Anton; Morisse, Filip
Highlights: Standardized assessment of the level of emotional development. Development of a short, psychometrically sound instrument for assessment in ID. Basis for better understanding of the respective behavior of persons with ID. Improvement of consistency and congruency when working with people with ID. Cross-cultural collaborative effort involving experts from different professions. Abstract: Background: Intellectual disability (ID) is often accompanied by delays in emotional development (ED) that may result in challenging behavior. Insight into emotional functioning is crucial for appropriate diagnostic assessment in adults with ID. However, few standardized assessment instruments are available. Aims: The aim of this study was to develop a short, psychometrically sound instrument for assessing levels of ED in individuals with ID: The Scale of Emotional Development – Short (SED-S), which can be applied to adults. Methods and procedures: The Scale for ED – Revised 2 (SED-R 2 ) was taken as a point of departure. In a first step, the validity and observability of the items ( N = 556) in the SED-R 2 were assessed by 30 experts from Germany, Belgium, and The Netherlands. The SED-S was then constituted in a consecutive consensus process, in which items to be included were selected based on their assessments and subsequently rephrased, and in which the structure and method of administering the new scale were agreed upon. Outcomes and results: The SED-S consists of 200 binary items describing five levels of emotional functioning (reference ages: 0–12 years) within eight domains: Relating to His/Her Own Body, Relating to Significant Others, Dealing with Change – Object Permanence, Differentiating Emotions, Relating to Peers, Engaging with the Material World, Communicating with Others, and Regulating Affect. Conclusions and implications: The SED-S offers an empirical-based, practical tool to assessing ED in adults with ID. Further research will be needed to meet the requirements of a standardized diagnostic instrument.